Champeta’s Heritage: Diasporic Music and Racial Struggle in the Colombian Caribbean - Juan D. Montoya Alzate (Transposition)
The shifts and fractures introduced by UNESCO heritagisation processes, unleashed in the Colombian Caribbean from the early noughties, have been particularly acute when it comes to music practices. Eight out of ten Colombian practices inscribed on UNESCO’s heritage lists are indeed either music-based or strongly music-related. This paper focuses on the ways in which champeta—an urban music-based identity crafted in the city of Cartagena from the mid-1980s—has engaged in official and unofficial processes of heritagisation, in which practitioners have struggled to revise the locally contested and racialized burden borne by their cultural practice. Delving into the Afrocentric aims laid out by Afro-descendants and pioneers of champeta music—born out of a Caribbean remake of “African” music styles such as soukous—this community-based heritagisation process reveals itself as unsympathetic to hegemonic power formations, hence challenging those involved in the creation of heritage lists. This paper problematizes the relation between tangible and intangible heritage in Cartagena by assessing the impact of implementing safeguarding measures in tangible landmarks particularly enmeshed in colonial and slave history. It also explores how multiculturalism and heritage have become scenarios for political struggle in Colombia, hence shaping social and academic grounds for discussing issues such as cultural ownership, racial identification, musical genealogies and political upheaval.